Implementation of conservation farming and its effect on farmers' income: A study on citrus farmers in Petung Sewu Village, Dau District, Malang Regency - Asnah Asnah; Pati Huka Melfinsius; Gunawan Indra Cakti (Agriekonomika, 2022)
This study aims to analyze the effect of applying vegetation and mechanical conservation on the income of citrus farmers. The method of determining the sample was simple random with a sample of 86 people. Data analysis used the income function model with multiple linear regression method. The results showed that the application of conservation that had a significant effect on income was the application of vegetation conservation, while other variables that had a significant effect were land area, plant maintenance costs, chemical fertilizer costs, pesticide costs and labor costs. The vegetation conservation is the best conservation, and profitable that is widely applied by farmers. This model has a significant effect on farmers' income with a significance level of 90 percent. Thus, the application of conservation adapts to land conditions, and increases the income of linear farmers with the ability of farmers to finance.